The effect of financial performance on firm value after the implementation of PSAK 73 concerning capitalization of leases (Lighthouse Publishing, 2022)
Through an increase in the selection of lease options in order to improve the company's financial performance and followed by the discovery of problems in reporting lease values ​​that do not appear in the company's financial statements, causing the need for new policies that can balance and overcome problems related to these leases. The purpose of this research is to see how a company's financial performance who have experienced the influence of the capitalization of leases related to the implementation of a new policy, namely PSAK 73 regarding leases, in influencing the firm value. This research uses the documentation method with secondary data in the form of annual financial reports from a sample of companies, namely the wholesale and retail sub-sector that are members of the Indonesian Stock Exchange (IDX), in the year of research, namely 2020. Testing the research hypothesis was carried out by partial parameter significance test (t-test) and a coefficient of determination test (R2). The results of the hypothesis testing show that the independent variables, namely the projected financial performance with Debt to Asset Ratio (DAR), Debt to Equity Ratio (DER), and fixed asset turnover each do not have a significant effect on the dependent variable, namely firm value with Tobin's Q projection. This happens because the average value of capitalized leases on the company's financial statements is low so the effect on firm value is also low and insignificant. This research is limited in using independent variables and the dependent variable used and the research sample only focuses on the wholesale and retail sub-sector. It is recommended for future research to choose independent variables and other dependent variables that can better describe the impact of implementing this new policy and use other samples of companies that also experience significant impacts related to capitalization of leases in order to describe better and different results.